Effect of parent concrete strength on recycled concrete performance - Bachir Kebaili; Mohammed Benzerara; Souad Menadi; Nadia Kouider; Redjem Belouettar (Fracture and Structural Integrity)
The reuse of concrete waste as a secondary aggregate could be an efficient solution for sustainable development and long-term environmental protection. However, the variable quality of waste concrete, especially with various compressive strengths, can have a negative effect on the final compressive strength of recycled concrete. In this approach, the major goal of this research is to study the effect of parent concrete qualities on the performance of recycled concrete. To accomplish this task, three grades of different compressive strengths (10 to 15) MPa, (20 to 25) MPa, and (30 to 40) MPa have been analyzed in an experimental test program, in which an unknown compressive strength is introduced as well. The experimental mix use 40% of secondary aggregates (both course and fine) and 60% of natural aggregates. This led to the decreasing of the compressive strength of the test concrete between 14% and 23.7% compared to the normal concrete. This loss was improved by adding an amount of cement equivalent to 4% of the weight of the recycled aggregate used. The achieved results prove that the strength properties of the parent concrete have a limited effect on the compressive strength of the recycled concrete. Additionally, low compressive strength parent concrete, when crushed, generates a high amount of fine aggregate and large percentage of recycled coarse aggregates with less attached mortar, and presents the same compressive strength as an excellent parent concrete.